Effect of process parameters on the microstructure and property of hydroxyapatite precursor powders and resultant sintered bodies. Issue 2 (8th September 2018) - Liu, Dan; Wu, Yonghao; Wu, Hongfeng; Li, Xiangfeng; Yang, Xiao; Zhu, Xiangdong; Zhang, Xingdong
Abstract: Nanocrystalline hydroxyapatite (HA) ceramic could have better potential in biomedical application due to its high bioactivity and mechanical strength. This study aimed at investigating on the relationship between the starting HA powders and resultant HA ceramics. The synthesized HA crystals using chemical precipitation showed different morphology, size, and crystallinity under different reaction temperature and aging time. The spray‐dried HA powders from the different HA slurries synthesized at 40, 60, and 80°C had spherical shapes and similar particles size but different specific surface area (SSA). Lower synthesizing temperature resulted in lower crystallinity and need‐like shape of the HA crystals, and thus higher SSA of the spray‐dried HA powders. After cold isostatic pressing of the HA powders, the HA green compacts were sintered at 1000, 1050, and 1150°C, respectively, and they presented different sinterability, compactness, and mechanical strength, which were tightly dependent on the starting HA powders. As compared to 80°C synthesized powders, 40 and 60°C synthesized powders exhibited better sinterability due to the lower crystallinity and higher SSA, leading to the relatively high compactness and mechanical strength, but small grain size below 100 nm of the resultant HA ceramics even at low sintering temperature of 1050°C.